2010
DOI: 10.1186/1741-7007-8-58
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high throughput sequencing-based small RNA discovery and discrete statistical biomarker analysis in a collection of cervical tumours and matched controls

Abstract: BackgroundUltra-high throughput sequencing technologies provide opportunities both for discovery of novel molecular species and for detailed comparisons of gene expression patterns. Small RNA populations are particularly well suited to this analysis, as many different small RNAs can be completely sequenced in a single instrument run.ResultsWe prepared small RNA libraries from 29 tumour/normal pairs of human cervical tissue samples. Analysis of the resulting sequences (42 million in total) defined 64 new human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
174
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(184 citation statements)
references
References 72 publications
5
174
1
2
Order By: Relevance
“…After identification in rat neurons (Kim et al 2004), miR-339 orthologs were identified in mouse and human tissue (Weber 2005). Expression profiling reports detection of miR-339 in adult hippocampus (Landgraf et al 2007), cervix (Witten et al 2010), placenta (Cummins et al 2006), and in numerous cancers (Kasashima 2004;Landgraf 2007;Stark et al 2010). MiR-339 is reported to regulate ICAM-1 (Ueda et al 2009), BCL6 , and μ-opioid receptor (Wu 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After identification in rat neurons (Kim et al 2004), miR-339 orthologs were identified in mouse and human tissue (Weber 2005). Expression profiling reports detection of miR-339 in adult hippocampus (Landgraf et al 2007), cervix (Witten et al 2010), placenta (Cummins et al 2006), and in numerous cancers (Kasashima 2004;Landgraf 2007;Stark et al 2010). MiR-339 is reported to regulate ICAM-1 (Ueda et al 2009), BCL6 , and μ-opioid receptor (Wu 2012).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-556 was first described in an expression profiling experiment with human colorectal cancer cells (Cummins 2006) and subsequently in other cancers including cervical and melanoma (Landgraf 2007;Stark 2010;Witten et al 2010), although its expression levels in all studies is very low. It is derived from intron 5 of the nitric oxide synthase 1 adaptor protein.…”
Section: Discussionmentioning
confidence: 99%
“…30 To assess the accuracy of CV, we estimated the FDR based on the number of classifiers (not shown). Choosing the top 40 miRNAs resulted in o15% FDR providing a rank order for miRNAs differentially expressed in all the specimens (not shown).…”
Section: Hierarchical Clustering Of the Specimensmentioning
confidence: 99%
“…For instance, Neely et al (2010) noted that a miR-21:miR-205 expression ratio can be used to distinguish invasive and non-invasive bladder tumors. In human cervical cancer cells, miR-205 was observed to be upregulated which leads to induced cell proliferation and migration by targeting two confirmed targets:CYR61 and CTGF (Witten et al, 2010;Xie et al, 2012).…”
Section: Mir-205 In Other Cancersmentioning
confidence: 99%